2005
DOI: 10.1007/s10512-005-0255-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation Measurement of the Neutron Spectra of the BARS-5, IGRIK, and YAGUAR Reactors

Abstract: A new approach is proposed and investigated for reconstructing the neutron spectra of reactors from activation measurements: the parameterization of the neutron spectrum is changed and the spectrum is represented in the form of a B spline. A Monte Carlo method is proposed for taking account of the distortions of the neutron spectrum by the measuring design of the detectors. The results of the activation measurements show that the approach developed can be used to reconstruct the neutron spectra of BARS-5, IGRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…It is evident that the group integrals with one another to within the limits of error. Evidently, the fluence and average energy of the spectra reconstructed in the present work are in good agreement with [15]. The largest reconstruction errors are observed that energy interval 0.1-1 MeV.…”
Section: E W E R E De ϕsupporting
confidence: 87%
See 4 more Smart Citations
“…It is evident that the group integrals with one another to within the limits of error. Evidently, the fluence and average energy of the spectra reconstructed in the present work are in good agreement with [15]. The largest reconstruction errors are observed that energy interval 0.1-1 MeV.…”
Section: E W E R E De ϕsupporting
confidence: 87%
“…The approach described above was used to reconstruct the spectra in the channels of the BARS-5, IGRIK, and YaGUAR reactors and on the surface of the IGRIK reactor using previous activation measurements (see [12] for the initial data). The activation reaction cross-sections were taken from the GSSD, IRDF-90, ENDF-B/VI, and ADL-3 libraries.…”
Section: E W E R E De ϕmentioning
confidence: 99%
See 3 more Smart Citations